2019
DOI: 10.20396/liames.v19i0.8656013
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Yurumanguí grammar and lexicon

Abstract: In this article, I offer a contribution to the philological study of premodern materials of languages of South America that have already become extinct. I am concerned with the Yurumanguí language, whose speakers were encountered in the 18th century in the western lowlands of Colombia by a Spanish expedition. This encounter resulted in the production of a short collection of words and phrases by a priest which is analyzed here anew. Problems of inconsistent and likely highly inadequate orthographic representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…113–116; Van Gijn & Muysken, 2020, p. 191). Analysis in Urban (2019b) has shown that a nasal–oral vowel contrast is likely for Yurumanguí, and aspects of the data are also consistent with the spread of nasal features across phonological domains. All this suggests an old coastal lowland‐Andes–Amazonia transect that may or may not dovetail with Pache's (2016) proposal for a geneaological connection between Chocoan and Pume (Yaruro).…”
Section: Relationships Due To Contactmentioning
confidence: 71%
See 3 more Smart Citations
“…113–116; Van Gijn & Muysken, 2020, p. 191). Analysis in Urban (2019b) has shown that a nasal–oral vowel contrast is likely for Yurumanguí, and aspects of the data are also consistent with the spread of nasal features across phonological domains. All this suggests an old coastal lowland‐Andes–Amazonia transect that may or may not dovetail with Pache's (2016) proposal for a geneaological connection between Chocoan and Pume (Yaruro).…”
Section: Relationships Due To Contactmentioning
confidence: 71%
“…In terms of language geography, isolates tend to occur not in the highest parts of the Andes at their respective latitudes, but rather at somewhat lower altitudes, especially on the eastern slopes. For the northern part of the Andes, they include Yurumanguí [yuru1242] in the Pacific‐facing lowlands of Colombia (Urban, 2019b) and Esmeraldeño (Atacame) [atac1235] on the coast of northern Ecuador (Adelaar, 2005). ‘Eastward‐facing’ isolates include Nasa Yuwe (Páez) [paez1247] in southern Colombia, Andaquí [anda1286] at still lower altitudes further east in the same area, Kamsá [cams1241] in southern Colombia east of Pasto and A'ingae (Cofán) [cofa1242] in the Colombian–Ecuadorian border area.…”
Section: Relationships Due To Common Descentmentioning
confidence: 99%
See 2 more Smart Citations